An Essay on Reading the Change of Cultural Heritage Components Through Semantic Literature: Historical Mesires in Istanbul - Secilmisler, Tore; Ozugul, Mehmet Doruk; Yerliyurt, Bora (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2015)
Since their first settlement historical cities have been changing due to both natural and social conditions. These changes also have reflections on cities' physical structures where they could be entirely traced. There are plenty conserved, changed and lost physical components in the old Ottoman capital Istanbul in time. It is known that several spatial elements, such as the residential buildings, public buildings, were either collapsed or lost. Mesires are also within these lost elements which represent information on Istanbul's recreation culture and green areas in the Ottoman Era. Thus, the aim of this study is to evaluate the change of mesire areas and recreation culture of Ottoman culture. Ottoman period, changes in Mesires are exemplified relating to some significant milestones and classified. In methodological terms, changes in Mesires are read within a semiological perspective considering denotative and connotative changes. Consequently, it is emphasized that Mesire culture and areas, which are inherited from Ottomans to today's Istanbul society, have changed and/or lost.
Keywords: Semiology; Istanbul; dennotative and connotative change; Mesire; Architecture